Allografting for Bosutinib, Imatinib, Nilotinib, Dasatinib, and Interferon Resistant Chronic Myeloid Leukemia without ABL Kinase Mutation - Uz, B.; Bektas, O.; Eliacik, E.; Goker, H.; Erbilgin, Y.; Sayitoglu, M.; Sayinalp, N.; Aksu, S.; Buyukasik, Y.; Ozcebe, O.; Haznedaroglu, I. C. (Case Reports in Hematology, 2011)
The current treatment of chronic phase chronic myeloid leukemia (CML) consists of oral tyrosine kinase inhibitors (TKIs). However, high-risk CML may present with an aggressive course which may result in blastic crisis or a “difficult-to-manage” state with available treatments. The aim of this paper is to report a patient with complicated CML resistant to treatment and progressed despite the administration of bosutinib, imatinib mesylate, nilotinib, dasatinib, interferon alpha 2a, cytotoxic chemotherapy, and allogeneic hematopoietic stem cell transplantation. The striking point of this case story is that no Abl kinase domain mutation against TKIs has been detected during this very complicated disease course of CML. Meanwhile, challenging cases will always be present despite the hope and progress in CML in the TKI era.